PENGARUH MACAM VARIETAS DAN DOSIS PUPUK ORGANIK PADAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH (Capsicum annum L.) THE EFFECT KIND VARIETY AND ORGANIC MANUREâ€S DOSAGE ON GROWTH AND YEILD CHILI (Capsicum annum L.) PENGARUH DOSIS PUPUK ORGANIK C - Mariono FP UTP Ska; Endang Suprapti; Tyas Soemarah Kurnia (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta)
The research mean to known the effect kind of variety and solid organic manureâ€™s dosage and the interaction of them towards the growth and natural result of red Chili. The research is carried out in Donohudan Village, Ngemplak District, Boyolali regency in an attitude of 96 meters about the sea level, using Regosol soil from March 8 until July 10 2006. The Research implements split plot trials with based pattern of Randomized Completed Block Desight (RCBD) which consists of two factors : (1) Kind of variety (V) as a primary treatment factor (main plot) (V1 = Hot Beauty ; V2 =Â TM 999; V3 = Prabu). (2) Dosage of manure 9D) as a secondary treatment factor (subplot) (D1 = tons / ha; D2 = 12 tons / ha; D3 = 14 Tons / ha). The research result : (1) kind of variety results the real differences fruits the plantâ€™s height, number of fruit red per plant, weight fruits per plot and the weight of green fruit per plot. It also real differences towards dry weight and fresh weight but it shows no difference at one which is bloomy, the weight of red fruits per plants, the weiht of green fruits per plot, amount of failing product per plost as weel as the weight weight of failing products. (2)The dosage of solid organic manure no real difference towards the plantâ€™s height. Fresh weight, the bloomy plants, the weight of red fruits per plant, amount of red nautral produch per plot, amount of filling product and the weight of filling product it shows, on the contrary, the real differences towards â€œbrangkasanâ€ dry weight, amount of green natural product and its weight as well as amount of red natural product per plot. (3) interction between both variety and solid organic manureâ€™s dosage non significant results ar entire research parameters. (4) The highest weight of red chili per plot is found in the combination V3D3 (Prabu variety 14 tons/ha) 17.417 kg/plot (24.2 tons/ha) and the lowest one is found in the combination V1D0 (Hot Beauty variety, solid organic manure), thatâ€™s is 12.597 kg/plot (17.5 tons/ha).